Phylogeographic origin of Helicobacter pylori is a determinant of gastric cancer risk. Issue 9 (25th February 2011) - de Sablet, Thibaut; Piazuelo, M Blanca; Shaffer, Carrie L; Schneider, Barbara G; Asim, Mohammad; Chaturvedi, Rupesh; Bravo, Luis E; Sicinschi, Liviu A; Delgado, Alberto G; Mera, Robertino M; Israel, Dawn A; Romero-Gallo, Judith; et al.
Abstract : Background and aims: Helicobacter pylori colonises the stomach in half of all humans, and is the principal cause of gastric cancer, the second leading cause of cancer death worldwide. While gastric cancer rates correlate with H pylori prevalence in some areas, there are regions where infection is nearly universal, but rates of gastric cancer are low. In the case of Colombia, there is a 25-fold increase in gastric cancer rate in the Andean mountain (high risk) region compared to the coastal (low risk) region, despite similarly high (∼90%) prevalence of H pylori in the two locations. Our aim was to investigate the ancestral origin of H pylori strains isolated from subjects in these high- and low-risk regions and to determine whether this is a predictive determinant of precancerous lesions. Methods: Multi-locus sequence typing was used to investigate phylogeographic origins of infecting H pylori strains isolated from subjects in the Pacific coast and Andes Mountains in the state of Nariño, Colombia. We analysed 64 subjects infected with cagA + vacA s1m1 strains. Gastric biopsy slides from each individual were scored for histological lesions and evaluated for DNA damage by immunohistochemistry. Results: We show that strains from the high-risk region were all of European phylogeographic origin, whereas those from the low risk region were of either European (34%) or African origin (66%). European strain origin was strongly predictive of increased premalignant histological lesions and epithelial DNA damage, even in the low-risk region; African strain origin was associated with reduced severity of these parameters. Conclusion: The phylogeographic origin of H pylori strains provides an explanation for geographic differences in cancer risk deriving from this infection.